Constraining glacier elevation and mass changes in South America - Braun, Matthias H.; Malz, Philipp; Sommer, Christian; Farias-Barahona, David; Sauter, Tobias; Casassa, Gino; Soruco, Alvaro; Skvarca, Pedro; Seehaus, Thorsten C. (My University, 2019)
Excluding the large ice sheets of Greenland and Antarctica, glaciers in South America are large contributors to sea-level rise(1). Their rates of mass loss, however, are poorly known. Here, using repeat bi-static synthetic aperture radar interferometry over the years 2000 to 2011/2015, we compute continent-wide, glacier-specific elevation and mass changes for 85% of the glacierized area of South America. Mass loss rate is calculated to be 19.43 +/- 0.60 Gt a(-1) from elevation changes above ground, sea or lake level, with an additional 3.06 +/- 1.24 Gt a(-1) from subaqueous ice mass loss not contributing to sea-level rise. The largest contributions come from the Patagonian icefields, where 83% mass loss occurs, largely from dynamic adjustments of large glaciers. These changes contribute 0.054 +/- 0.002 mm a(-1) to sea-level rise. In comparison with previous studies(2), tropical and out-tropical glaciers - as well as those in Tierra del Fuego - show considerably less ice loss. These results provide basic information to calibrate and validate glacier-climate models and also for decision-makers in water resource management(3).
Keywords: Elevation (ballistics); Glacier mass balance; Glacier morphology; Future sea level